Sedation and Anesthesia in Gastrointestinal Endoscopy: Indian Scenario - Shah, Apurva; Bohra, Shravan; Shah, Megha (Journal of Digestive Endoscopy, 2019)
Sedation in endoscopy is a drug-induced depression in the level of consciousness. Traditionally, the sedation regime most commonly used for conscious sedation during gastrointestinal (GI) endoscopy was a combination of opioids and benzodiazepines. However, in the last two decades, propofol is regarded as the sine qua non agent for gastroenterological endoscopic sedation. A thorough risk evaluation before the procedure and monitoring during the procedure are paramount. In elective endoscopy, unplanned adverse events are rare, occurring in 1.4% of procedures. All currently available guidelines state that the endoscopist is not permitted to administer propofol and to monitor the patient. This task must be done by an additional person, who has the sole responsibility of administering the sedative and monitoring the patient. Various scoring systems exist for defining the discharge criteria, of which the Aldrete score is the most commonly used.
Keywords: sedation; GI endoscopy; propofol; Aldrete score